A community-based oral health promotion model for HIV patients in Nairobi, East District in Kenya: a study protocol - Lucina N. Koyio; Wil J.M. van der Sanden; Andre van der Ven; Jan Mulder; Nico H.J. Creugers; Matthias A.W. Merkx; Jo E. Frencken (SAGE Publishing, 2013)
Background: General HIV-related orofacial lesions, most commonly oropharyngeal candidiasis, have a typical clinical appearance and can be recognised by members of the community. Although affected patients often experience pain leading to compromised eating and swallowing, barriers such as social stigma and lack of knowledge regarding available services may prevent them from seeking early care. Educating the community about these lesions through community health workers (CHWs) who are democratically elected community members may encourage individuals affected to seek early oral health-care in the health facilities. A health facility (HF) is a health centre mainly run by clinical officers (CO), i.e. personnel with a 3-year medical training, and nurses. This study aims to evaluate the effect of a CHW training programme on: i) their knowledge and recognition of HIV-related oral-facial lesions at a community level; and ii) referral of affected patients from the community to the HFs. Design and Methods: All 800 CHWs in 2 administrative divisions of Nairobi East District (test group n=400; control group n=400) will be selected. The test group will receive training. CHWs in both groups will be assessed at 4 time points: −3, 0, +3 and +6 months with reference to the training on: i) their knowledge of HIV-related orofacial lesions (using a written questionnaire); and ii) their performance in referring affected patients to the HFs (using clinical data). Expected Impact: Early recognition of HIV-related orofacial lesions at a community level will prompt community members to seek early oral care, leading to early HIV testing and counselling regarding failure of antiretroviral therapy, while treatment outcomes are still favourable.